Gender dimension of globalization : a survey of the literaure with a focus on Latin America and the Caribbean - Thorin, Maria (ECLAC SantiagoCL, 2001)
Presents a critical survey of literature on economic globalization and gender with specific focus on Latin American and Caribbean studies. Includes topics such as the concept of globalization; gender differentiated effects of labour flexibilization and informalization; the empowerment potential of women's trade-related employment; gendered impacts of the weakening of the state under globalization; modern technologies and women; international migration and, the global sex industry and women.